Pingit Film: A Problematic Expression of the Distortion of Javanese Traditional Wedding Traditions - Pahlevi, Riza; Wiranegara, IGP (Seni Media Rekam ISI Surakarta, 2024)
Pingit Film is the manifestation of the tradition of ‘pingit’ that has been adapted and/or eroded by modernization. This work is created in addition to being an entertainment medium, it also contains messages that ‘pingit’ that is not in accordance with the existing standards will make the purpose blurred. The process of creating this film combines the concepts of realism and surrealism. This combination is intended to give a clear limit to the character’s mind. The audience is invited not only to watch and listen, but also to feel what is in the mind of the character, indecision, doubt, overthinking, negative thinking because of the things he has just experienced. This experience poured into the form of sound and images, in this context is lighting and color grading. This work is certainly a form of contribution to the treasures of science and art.